Towards the Magic Radioactive Bullet: Improving Targeted Radionuclide Therapy by Reducing the Renal Retention of Radioligands - Kim E. de Roode; Lieke Joosten; Martin Behe (Pharmaceuticals, 2024)
Targeted radionuclide therapy (TRT) is an emerging field and has the potential to become a major pillar in effective cancer treatment. Several pharmaceuticals are already in routine use for treating cancer, and there is still a high potential for new compounds for this application. But, a major issue for many radiolabeled low-to-moderate-molecular-weight molecules is their clearance via the kidneys and their subsequent reuptake. High renal accumulation of radioactive compounds may lead to nephrotoxicity, and therefore, the kidneys are often the dose-limiting organs in TRT with these radioligands. Over the years, different strategies have been developed aiming for reduced kidney retention and enhanced therapeutic efficacy of radioligands. In this review, we will give an overview of the efforts and achievements of the used strategies, with focus on the therapeutic potential of low-to-moderate-molecular-weight molecules. Among the strategies discussed here is coadministration of compounds that compete for binding to the endocytic receptors in the proximal tubuli. In addition, the influence of altering the molecular design of radiolabeled ligands on pharmacokinetics is discussed, which includes changes in their physicochemical properties and implementation of cleavable linkers or albumin-binding moieties. Furthermore, we discuss the influence of chelator and radionuclide choice on reabsorption of radioligands by the kidneys.